The Role of HMGB1and KIM-1 Repair Genes in the Progression of Kidney Failure Disease - Alyaa Abdulhadi Salih; Kareem Hamed Ghali (Institute of Medico-legal Publications Pvt Ltd, 2021)
Renal Failure(RF) is a leading clinical characteristic of patients in nephrology , it represents significantconcern and the main challenge for healthcare systems. The incidence rate of RF is rising globally , mainlyas a result of increased aging population. The current study , was performed to identify the effect ofHMGB1and KIM-1gene expression in renal failure disease focusing on it is role on the repair processes.This study comprises 100 patients diagnosed clinicaly and seriologicaly with renal failure )52 males and 48females ) their age vary from (17 to 80 years) and 30 healthy individuals as a control group( 18 males and12 females ). RNA extracted from blood samples and converted to cDNA which subjected to real-time PCRfor detection gene expression .HMGB1 and KIM-1 have significantly overexpression (3.51 folds and 5.37folds ) respectively in RF patients compared with healthy control subjects ( p <0.05). However , HMGB1and KIM-1 gene folding elevated gradually with advance the severity of the RF disease.